The oasis: a story of displacement and resistance (2017)
This text describes the result of a participatory project I carried out in July 2015, in Moravia, a neighborhood located in Medellin, Colombia. The contemporary art center ‘Fundación Casa 3 Patios’ and the Colombian Ministry of Culture aided the initiative; the former is an organization that researches pedagogy with social impact, alternative art, participatory town planning, architecture and curatorship. The project’s main purpose was to experiment with creative activities that could bring forth consequences of accountability in the community; consequently, the practice-based research started with a collective exploration of the neighborhood from the perspective of emotional cartographies and ephemeral urban interventions, which entailed understanding Moravia’s territory as the display of a web of human interactions that was interpreted from a psychogeographical perspective, that is to say, as the manifestation of desires, fears, impulses, conflicts, etc. This project is part of a long-term practice-led research that investigates how artistic, design and humanistic appropriations of public space can inspire collective agency and positive transformations in neglected scenarios. In these situations the ephemeral interventions represent a pretext for activating a given social dynamic, rather than being the main goal of the research.